Effect of vitamin E on the development of atherosclerosis - KARTAL ÖZER, NESRİN (My University, 2000)
The development of atherosclerosis is a multifactorial process in which both elevated plasma cholesterol levels and proliferation of smooth muscle cells play a central role. Numerous studies have suggested the involvement of oxidative processes in the pathogenesis of atherosclerosis and especially of oxidised low density lipoproteins. Some epidemiological studies have shown an association between high dietary intake or high serum concentrations of vitamin E and lower rates of ischemic heart disease. Recently, the Cambridge Heart Antioxidant Study (CHAOS) reported strong protection by high vitamin E doses against the risk of fatal and non fatal myocardial infarction. Here we have shown that incubation of vascular smooth muscle cells in the presence of alpha-tocopherol resulted in inhibition of cell proliferation and protein kinase C activity. Since beta-tocopherol and probucol are not inhibitory, the effect of alpha-tocopherol is considered due to a non-oxidant mechanism. In order to understand the protective role of alpha-tocopherol against atherosclerosis in vivo the following rabbit studies were carried out. Atherosclerosis was induced by a vitamin E poor diet containing 2% cholesterol in a group of rabbit. The other groups had 2% cholesterol in the diet plus 50 mg/kg vitamin E i.m. or 1% probucol or 50 mg/kg vitamin E plus 1% probucol. After 4 weeks, aortas were removed and analysed by microscopy for atherosclerotic lesions. Samples of the media were analysed for protein kinase C activity. The aortas of cholesterol-fed rabbits showed typical atherosclerotic lesions, detected by microscopic examination, their media smooth muscle cells exhibited an increase in protein kinase C activity. Vitamin E fully prevented cholesterol induced atherosclerotic lesions and the induction of protein kinase C activity while probucol was not effective. These results show that the protective effect of vitamin E against hypercholesterolemic atherosclerosis is not produced by an other antioxidant such as probucol and, therefore, may not be linked to the antioxidant properties of this vitamin. The effects observed at the level of smooth muscle cells in vitro and ex-vivo suggests an involvement of signal transduction events in the protective effect of vitamin E against atherosclerosis.
Keywords: Animals; Male; Cell Line; Dose-Response Relationship, Drug; Cholesterol; Rabbits; Vitamin E; Arteriosclerosis; Cholesterol, Dietary; Muscle, Smooth, Vascular; Protein Kinase C; Cell Division; Anticholesteremic Agents; Probucol